2017
DOI: 10.1016/j.jcat.2016.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Gas phase oxidation of furfural to maleic anhydride on V 2 O 5 /γ-Al 2 O 3 catalysts: Reaction conditions to slow down the deactivation

Abstract: An alumina-supported vanadium oxide catalyst (13.9 wt. % of vanadium oxide) has been tested on the gas phase oxidation of furfural and characterised by different techniques. These studies have showed that catalyst unavoidably deactivates by deposition of maleates and resins over the surface. Full regeneration is accomplished by burning off these deposits at 773 K. The studies have also demonstrated that if the primary contact occurs at temperatures at which furfural conversion is low and then the temperature i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 36 publications
0
36
0
Order By: Relevance
“…MAnh is a key chemical intermediate employed for the production of lubricant additives, unsaturated polyester resins, pharmaceuticals, plasticizers, etc. 21,26,[37][38][39][40][41][42] At present, MAnh is industrially manufactured via the gas phase oxidation of benzene and n-butane at high temperatures. 40 Considering the increasing depletion of fossil sources and chemical sustainability, the production of MAnh using renewable biomass derivatives as the starting materials is highly promising.…”
Section: Catalytic Conversion Of Furfural Into Value-added Chemicalsmentioning
confidence: 99%
“…MAnh is a key chemical intermediate employed for the production of lubricant additives, unsaturated polyester resins, pharmaceuticals, plasticizers, etc. 21,26,[37][38][39][40][41][42] At present, MAnh is industrially manufactured via the gas phase oxidation of benzene and n-butane at high temperatures. 40 Considering the increasing depletion of fossil sources and chemical sustainability, the production of MAnh using renewable biomass derivatives as the starting materials is highly promising.…”
Section: Catalytic Conversion Of Furfural Into Value-added Chemicalsmentioning
confidence: 99%
“…In the last years different conversion routes have been technically demonstrated to turn this petrochemical into a renewable chemical by the oxidation of different renewable platforms like 1-butanol [69], levulinic acid [70], HMF [33,[71][72][73] and FF [13,31,[74][75][76][77][78][79][80][81] using O 2 (see Table 4). Moreover, contrary to the current conventional process carried out in the gas phase, depending on the reaction conditions and the used reactant, the MAN production can be performed in the aqueous or gas phase.…”
Section: Anhydride Of Acids: Maleic Anhydride (Man)mentioning
confidence: 99%
“…Finally, oxidation of FF in the gas phase is also reported using different vanadium oxide-based catalysts (V oxide, V-Mo and V-Bi mixed oxides); however, most of the references date from the first part of the 20th century [31,89,[94][95][96]. More recently, López-Granados et al has reported some promising results [31,89] using vanadium oxide supported on alumina. Thus, at 300 • C and using 1% of FF in air (vol%) and a O 2 /FF molar ratio of 20, an initial yield well above 70% was obtained.…”
Section: Anhydride Of Acids: Maleic Anhydride (Man)mentioning
confidence: 99%
See 1 more Smart Citation
“…The best conditions of reaction were at 573 K using 1 vol.% furfural and 20 vol.% O 2 , to obtain 60% of maleic anhydride yield after 15 of reaction. Therefore, the high oxidizing potential of the reaction mixture favor the selective transformation to maleic acid and to prevent resin and maleate formation and subsequent deactivation [70].…”
Section: Oxidationmentioning
confidence: 99%